COMPARATIVE OUTCOMES OF MULTIVESSEL PERCUTANEOUS CORONARY INTERVENTION VS. STAGED PERCUTANEOUS CORONARY INTERVENTION IN PAKISTANI PATIENTS WITH COMPLEX CORONARY ARTERY DISEASE - Dr Syed Muzammil Shah; Dr Honey Raj Vishno; Dr Tariq Shah; Dr Muhammad Abdul Wahab; Dr Rafi Ullah; Dr Fahad Liaqat (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Coronary artery disease (CAD) is a major cause of morbidity and mortality globally, particularly in developing countries like Pakistan. Percutaneous coronary intervention (PCI) is a widely used revascularization strategy for complex coronary artery disease, but the optimal approach—whether multivessel PCI or staged PCI—remains under debate. This study aims to evaluate the comparative outcomes of these two strategies in Pakistani patients with complex coronary artery disease.Objective: To compare the outcomes of multivessel PCI versus staged PCI in terms of mortality, major adverse cardiac events (MACE), and procedural complications in Pakistani patients with complex coronary artery disease.Methods: This retrospective observational study was conducted at Hayatabad Medical Complex, Peshawar, Pakistan, from January 2018 to December 2021. The study included 303 patients aged 40 to 80 years with multivessel coronary artery disease who underwent either multivessel PCI or staged PCI. Data were collected from medical records, and statistical analysis was performed using SPSS version 26.0. Kaplan-Meier survival curves and log-rank tests were used to compare time-to-event data.Results: There were no significant differences in in-hospital mortality, 30-day mortality, and MACE at 6 months between multivessel PCI and staged PCI. The in-hospital mortality rate was 3.2% for multivessel PCI and 2.8% for staged PCI, while the 30-day mortality rate was 5.1% and 4.7%, respectively. MACE at 6 months was 12.5% for multivessel PCI and 11.8% for staged PCI. However, multivessel PCI was associated with a higher incidence of contrast-induced nephropathy (9.2% vs. 6.8%, p < 0.05) and longer hospital stays (5.4 days vs. 4.1 days, p < 0.05).Conclusion: Multivessel PCI and staged PCI show comparable outcomes in terms of mortality and MACE in Pakistani patients with complex coronary artery disease. However, multivessel PCI is associated with higher procedural complications, emphasizing the need for careful patient selection and management. These findings support personalized treatment strategies to optimize patient outcomes.